연골종으로 오인된 경막내 요추 추간판 탈출증 - 이수빈(Soo-Bin Lee); 정수일(Su-Il Jung); 안상정(Sangjeong Ahn); 김상희(Sang hee Kim) (The journal of the Korean Orthopaedic Association, 2023)
추간판 수핵은 연골 조직과 연골 세포로 이루어져 있어 연골종과 조직학적 소견이 유사하다. 경막내 추간판 탈출증은 경막내 종양의 형태로 관찰될 수 있으며, 연골종과 같은 조직학적 소견을 보인다면 경막내 추간판 탈출증을 염두에 두어야 한다. 저자들은 1 차 병리 소견이 연골종이었던 경막내 종괴를 수술 소견을 종합하여 경막내 추간판 탈출증으로 최종 진단한 증례를 문헌 고찰과 함께 보고하고자 한다. The intervertebral disc nucleus pulposus is composed of cartilage tissue and chondrocytes, and histological findings are similar to those of a chondroma. Intradural disc herniation can be observed in the form of an intradural tumor. Hence, if histological findings such as chondromas are observed, intradural disc herniation should be considered. The authors report a case in which the primary pathological finding was intradural chondroma and it was finally diagnosed as an intradural disc herniation based on the surgical findings. KCI Citation Count: 0